Exploring Mental Disorders in the Serial Dynamics of Slasher Series on Cable TV - Ahmad Hayat (Series. International journal of tv serial narratives, 2025)
This article examines the industrial conditions that inform contemporary representations of mental disorders in cable slasher television series. Drawing upon interviews with network showrunners and executives, the paper illustrates the role of serialization in shaping mentally ill characters and the ways in which certain narrative strategies are employed to explore their perceptions and rationalize their behaviors. With a focus on two case studies, A&E’s Bates Motel (2013–2017) and MTV’s Scream: The TV Series (2015–2016), the inspection suggests that the shows provide depictions to address their producing institutions’ audience-targeting objectives and therefore propose the significance of seeking mental care for such conditions.